O efeito da concentração de matéria orgânica sobre a densidade energética e o bem estar geral de peixes exploradores de fundo. - Zanatta, Naiara (2013)
Aiming to contribute to the understanding of the participation of bottom feeder fishes in energy use in the chain of detritus, this study aimed to answer the following questions: a) Does have the amount of organic matter in the sediment a positive effect on the density energy and condition factor of fish explorers background? b) Is the variation in the energy density of P. lineatus associated with variation in amount of fine particles of organic detritus and L. platymetopon to coarse? c) What abiotic factors influence the energy density and condition factor of P. lineatus and L. platymetopon? Sediments and fish species were collected in five lakes in the floodplain of the upper Paraná River, between September 2011 (dry season) and February 2012 (rainy season). Nonparametric Spearman correlations were used to assess the relationship between organic matter (total, fine and coarse), energy density, and condition factor. The same analysis was used to investigate the influence of abiotic factors on the energy density and condition factor of the species analyzed. It was concluded that the concentration of organic matter varied temporally with higher values recorded in the rainy season, with the predominance of coarse particles. We observed a negative correlation between the total organic matter and energy density of L. platymetopon in drought, and positive between the somatic condition factor (Kn) of P. lineatus and organic matter in the rainy season. Electric conductivity, total nitrogen, and phosphate influenced the energy density of P. lineatus in drought, while the pH influenced the L. platymetopon. The Kn of P. lineatus was correlated with dissolved oxygen during the flood period, the pH and conductivity correlated with Kn of L. platymetopon only in the dry. The organic matter, fine and coarse, did not influence the energy density and Kn of both species differently. The lack of correlation observed between the concentration of organic matter and energy density of bottom feeder fishes does not allow us to accept the hypothesis formulated for this study. It can be argued that the energy balance of bottom feeder fishes appears to be more complex that induces us to think, the direct relationship between food availability and energy accumulation in the muscle.